Solve for p p^2-5p-6=0

Math
p2-5p-6=0
Factor p2-5p-6 using the AC method.
Tap for more steps…
Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -6 and whose sum is -5.
-6,1
Write the factored form using these integers.
(p-6)(p+1)=0
(p-6)(p+1)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
p-6=0
p+1=0
Set the first factor equal to 0 and solve.
Tap for more steps…
Set the first factor equal to 0.
p-6=0
Add 6 to both sides of the equation.
p=6
p=6
Set the next factor equal to 0 and solve.
Tap for more steps…
Set the next factor equal to 0.
p+1=0
Subtract 1 from both sides of the equation.
p=-1
p=-1
The final solution is all the values that make (p-6)(p+1)=0 true.
p=6,-1
Solve for p p^2-5p-6=0

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top